Efektivitas Program Dana Desa Di Desa Ngabar Kecamatan Siman Kabupaten Ponorogo - Nurrochmat Yusuf; Muchtar; Khoiruddin (Journal of Public Power, 2021)
Village funds are a mandate that must be conveyed to the village community, program effectiveness and village fund management are a reference for success in the program to improve the welfare of rural communities. The aim of this research is to analyze the implementation, effectiveness and impact of the village fund program in Ngabar Village, Siman District, Ponorogo Regency. This study uses qualitative, the main data sources in this study are the words and actions of who will be interviewed. The rest is additional data such as photos, certificates, documents and others. This study uses data collection techniques in the form of interviews (interviews), documentation, and observations, both directly and involved (participant observation). The results of the research are as follows, that the village fund program in the village of Ngabar, Siman District, Ponorogo Regency in 2020 runs very effectively with the suitability of financial management based on Permendagri No. 113 of 2014, the implementation of the village fund program in Ngabar village, Ponorogo district, can be categorized as quite effective. With the resource approach, process approach, and goals approach, and that the village fund program has had a positive impact in empowering the people of Ngabar Village, Siman District, Ponorogo Regency. These impacts can be seen in the realization of the village fund program in Ngabar village in 2020.